No. 1 2-SON DEKABR, 2025 -YIL MARKETING DETERMINANTS OF FORMING TRUST IN PRODUCTS IN DEVELOPING MARKETS (Marketing Journal, 2025)
This article presents the results of an analysis of key marketing determinants influencing the development of trust in products in emerging markets. A model of trust determinants is constructed by systematizing factors such as brand reputation, information noise, enterprise business orientations, and modern technological tools. The triad of Purchase Satisfaction, Trust, and Consumer Loyalty is examined, and an algorithm for the interaction of the triad's constructs is proposed. The purpose of the study is t o determine the impact of personalized marketing on the development of trust among consumers in the market. Graphs and tables are also presented, reflecting the structure of trust factors and their interrelationships.
Keywords: marketing determinants; emerging markets; product quality; consumer; retailer; satisfaction; trust; loyalty